Feeding value of four different hybrid sorghum grains for finishing cattle - McCollough, R.L.; Drake, C.L.; Schalles, R.R.; Roth, G.M.; Harrison, K.F. (Kansas State University. Agricultural Experiment Station, 2011)
Hybrid sorghum grain is the major source of energy in livestock finishing rations in the Midwest. In 1969, 739 million bushels of sorghum grain were produced in the United States and 620 million bushels, or 84% were fed to livestock. Kansas ranked second to Texas, producing 183 million bushels in 1968, or 30% of the quantity fed to livestock. Since hybrid sorghum grains ware introduced in 1956, yield has increased 25%. Because livestock consumes 84% of the sorghum grain produced in the United States, hybrids with superior nutritive value would be advantageous.
Keywords: Beef; Feed value; Sorghum grain; Finishing cattle